The role of the European Court of Justice in the process of European integration : a neofunctionalist analysis - Lin, Yu-Chou (My University, 2020)
This thesis evaluates the role of the European Court of Justice (ECJ) in theprocess of European integration under Neofunctionalism. The main argument of thethesis is that the ECJ, as an autonomous political actor, has successfully influencedthe Union’s policies, changed the political elites’ preferences, and made substantialcontributions to creating legal principles to foster and maintain the momentum ofEuropean integration under the Neofunctional logic, especially the notion of spillover.Chapter 1 introduces various narratives of the role of the ECJ and the notion ofspillover under Neofunctionalism. Neofunctionalism is taken as the primarytheoretical framework to analyze the role of ECJ during European integration in thisthesis. Chapter 2 offers an overview of the ECJ and assesses the role of the ECJ undera Neofunctionalist analysis. Chapter 3 provides two legal principles elucidated by theECJ within the integration process: ‘the mutual recognition principle’ and ‘the right tobe forgotten.’ These principles corroborate that the ECJ produces spillovers toinfluence European integration. The thesis concludes that the role of the ECJ nicelydovetails with the concept of spillover under Neofunctionalism and that the ECJproduces spillover effects, which have successfully influenced the European Union’spolicies.

Divanı'nın (ABAD) Avrupa entegrasyonu sürecindeki rolünü değerlendirmektedir. Butezin temel argümanı, özerk bir siyasi aktör olarak ABAD’ın Birliğin politikalarınıbaşarıyla etkilediği, siyasi elitlerin tercihlerini değiştirdiği ve Avrupa Birliği'neentegrasyonun ivme kazandırılması ve sürdürülmesi için yasal ilkelerinoluşturulmasında ve de özellikle Neofonksiyonel mantık çerçevesinde ‘spillover/ yayılma’ kavramına önemli katkılarda bulunduğudur. Tezin ilk bölümü, ABAD'ınçeşitli rol anlatımlarını ve Neofonksiyonalizm çerçevesinde ‘spillover/ yayılma’kavramının açıklamaktadır. Bu tez, Neofonksiyonalizmi temel teorik çerçeve alarak,Avrupa entegrasyonu sürecinde ABAD'ın rolü analiz etmektedir. Tezin ikinci bölümü,ABAD'a genel bir çerçeve sunar ve Neofonksiyonel analiz kapsamında ABAD'ınrolünü değerlendirmektedir. Tezin üçüncü bölümü, ‘karşılıklı tanıma ilkesi’ ve‘unutulma hakkı’ olmak üzere ABAD'ın Avrupa entegrasyonunu etkilemek içinspillover/ yayılma ürettiğini doğrulamak amacıyla iki belirgin örnek sunmaktadır. Builkeler ABAD’ın Avrupa entegrasyonunu etkilemek için spillover/ yayılmalarürettiğini doğrulamaktadır. Bu çalışma, Neofonksiyonalizm çerçevesinde ABAD'ınAvrupa Birliği politikalarını başarılı bir şekilde etkileyen spillover/ yayılma etkileriyarattığı sonucuna varmıştır.
Keywords: ABAD; Avrupa Birliği; ECJ; European Integration; European Union; International relations; Neofunctionalism; Political science; Siyasal bilim; Spillover Neofonksiyonalizm; spillover/ yayılma etkileri; Uluslararası ilişkiler